Biomass Production and Root Distribution of Acacia lenticularis (L.) Willd under an Agrisilvicultural System in North-West Alluvial Plain of Bihar - Chaturvedi, O.P.; Das, D.K.; Chakraborty, A.K. (Indian Journal of Agroforestry, 2020)
A study of an agrisilviculture system comprising A. lenticularis and turmeric (Curcuma domestica) local cv. Rajendra Sonia was conducted. Above and below ground biomass production and distribution of coarse and fine roots were studied in 4-year-old A.lenticularis planted at a spacing of 2 x 2 m, 2 x 3 m, 2 x 4 m and 2 x 5 m. The shoot biomass varied from 22.0 t ha-1 to 30.0 t ha-1 depending on the tree density. Among the different above ground tree components, stem wood contributed maximum biomass (62.5-70.4 %), followed by branches and leaves. Root distribution pattern showed that most of the coarse roots were distributed in the top 40 cm of soil, whereas fine roots were concentrated in the top 20 cm. Coarse root biomass decreased with an increase in spacing. The spread of roots was asymmetrical in trees planted at 2 x 2 m and 2 x 3 m spacing, while it was symmetrical in trees planted at wide spacing. No significant difference was observed in the fine root biomass in different stands. The root: shoot ratio increased with an increase in spacing. Yield of turmeric varied significantly from 160 q ha-1 to 220 q ha-1 and it increased with a decrease in tree density. This study suggested that A. lenticularis has potential for improving the fertility status of the soil, but when grown with turmeric could need pruning of their lateral roots.